Recombinant von Willebrand factor for severe gastrointestinal bleeding unresponsive to other treatments in a patient with type 2A von Willebrand disease: a case report - Brown, Racquel (Blood Coagul Fibrinolysis, 2017)
A recombinant von Willebrand factor (rVWF) was recently approved in the United States for on-demand treatment and control of bleeding episodes in adults with von Willebrand disease (VWD). In contrast to plasma-derived VWF products available in the United States, rVWF does not contain factor VIII (FVIII). To date, there is no published experience of rVWF in clinical practice. We report the acute and prophylactic use of rVWF in a patient with VWD type 2A and severe gastrointestinal bleeding. Dosing with plasma-derived VWF/FVIII concentrates was constrained by FVIII accumulation; the bleeding was unresponsive, and multiple red blood cell transfusions were required. After initiation of rVWF (4200 IU every other day), bleeding symptoms subsided, and no red blood cell transfusions were required during more than 3 months of prophylactic therapy (most recent dosage: 2800 IU every other day). rVWF may be effective in the prevention, as well as treatment, of severe bleeding symptoms in VWD.